Safranal prevents rotenone-induced oxidative stress and apoptosis in an in vitro model of Parkinson’s disease through regulating Keap1/Nrf2 signaling pathway - Pan, P-K.; Qiao, L-Y.; Wen, X-N (Cellular and Molecular Biology, 2016)
Safranal, a major constituent of saffron, possesses antioxidant and anti-apoptotic properties showing considerable neuroprotective effects. However, whether safranal shows therapeutic effect on Parkinson’s disease (PD) remains unknown. In this study, we aimed to investigate the potential effect of safranal on PD using an in vitro model of PD induced by rotenone. We found that safranal significantly inhibited rotenone-induced cell death in a dose-dependent manner. Moreover, safranal also markedly suppressed the reactive oxygen species (ROS) generation and cell apoptosis induced by rotenone. Further investigation showed that safranal inhibited the expression of kelch-like ECH-associated protein 1 (Keap1) and promoted the nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) in rotenone-induced dopaminergic neurons. Meanwhile, the downstream antioxidant enzyme genes of Nrf2 including glutathione S transferase (GST), glutamate-cysteine ligase catalytic subunit (GCLc), NADPH-quinone oxidoreductase 1 (NQO1) and heme oxygenase1 (HO-1) were also induced by safranal in rotenone-induced dopaminergic neurons. However, the knockdown of Nrf2 significantly abrogated the protective effect of safranal on rotenone-induced neurotoxicity. Taken together, our study suggests that safranal protects against rotenone-induced neurotoxicity associated with Nrf2 signaling pathway implying that safranal may serve as a potent and promising therapeutic drug for the treatment of PD.